Downwardly mobile : the changing fortunes of American realism - Lawson, Andrew, 1959 July 4- (New York ; Oxford : Oxford University Press, 2012)
This title explores the links between a growing sense of economic precariousness within the American middle class and the development of literary realism over the course of the nineteenth century, as it examines works by Rebecca Harding Davis, William Dean Howells, Henry James, Hamlin Garland, and others.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Keywords: Realism in literature; American fiction -- 19th century -- History and criticism; American fiction -- 20th century -- History and criticism; Economics in literature; Financial crises in literature; Social mobility in literature; Social classes in literature; United States -- Economic conditions -- 19th century